Assessing potential impacts of shale gas development on shallow aquifers through upward fluid migration: A multi-disciplinary approach applied to the Utica Shale in eastern Canada. (February 2019) - Rivard, C.; Bordeleau, G.; Lavoie, D.; Lefebvre, R.; Ladevèze, P.; Duchesne, M.J.; Séjourné, S.; Crow, H.; Pinet, N.; Brake, V.; Bouchedda, A.; Gloaguen, E.; et al.
Abstract: Potential impacts of shale gas development on shallow aquifers has raised concerns, especially regarding groundwater contamination. The intermediate zone separating shallow aquifers from shale gas reservoirs plays a critical role in aquifer vulnerability to fluid upflow, but the assessment of such vulnerability is challenging due to the general paucity of data in this intermediate zone. The ultimate goal of the project reported here was to develop a holistic multi-geoscience methodology to assess potential impacts of unconventional hydrocarbon development on fresh-water aquifers related to upward migration through natural pathways. The study area is located in the St. Lawrence Lowlands (southern Quebec, Canada), where limited oil and gas exploration and no shale gas production have taken place. A large set of data was collected over a ∼500 km 2 area near a horizontal shale gas exploration well completed and fracked into the Utica Shale at a depth of ≈2 km. To investigate the intermediate zone integrity, this project integrated research results from multiple sources in order to obtain a better understanding of the system hydrodynamics, including geology, hydrogeology, deep and shallow geophysics, soil, rock and groundwater geochemistry, and geomechanics. The combined interpretation of the multi-disciplinary dataset demonstrates that there is no evidence of, and a very limited potential for, upward fluid migration from the Utica Shale reservoir to the shallow aquifer. Microbial and thermogenic methane in groundwater of this region appear to come from the shallow, organic-rich, fractured sedimentary rocks making up the regional aquifer. Nonetheless, diluted brines present in a few shallow wells close to and downstream of a normal fault revealed that some upward groundwater migration occurs, but only over a few hundred meters from the surface based on the isotopic signature of methane. The methodology developed should help support regulations related to shale gas development aiming to protect groundwater. Highlights: This synthesis presents results and benefits from using multi-disciplinary data. Integrated shallow and deep datasets allowed a holistic study of potential upflow. Dissolved methane is present throughout the study area, locally at high levels. Microbial and thermogenic methane in groundwater come from the shallow rock aquifer. There is no evidence of upward fluid migration over large vertical distances.